ENGLISH â€“ INDONESIAN TRANSLATION METHODS IN THE SHORT STORY â€œA BLUNDERâ€ BY ANTON CHEKHOV - Aditya Nugraha; Muhammad Aprianto Budie Nugroho; Yudi Rahman (Indonesian EFL Journal, 2017)
This study contains analysis of translation method in the short story â€œA Blunderâ€ by Anton Chekhov which is translated into Indonesian by students as the participants of this research. In translation analysis processes, the researcher used theory of translation method based on Newmark Theory. While to find out the equivalence in the translation, the researcher used Baker Theory. The researcher thought that there are a lot of variations methods appear in the results of translation, so he wants to know the kinds of equivalence translation used by the participants to make the target language (TL) more comprehensible. Qualitative descriptive method that includes observation and document analysis was used in this research. Here, the result of document analysis were consulted to the translation and literature expertise to check the result of the analysis. As the conclusion, the researcher finds 6 methods used by the participants to render the short story â€œA Blunderâ€ into the target language (TL). Besides, the researcher finds two kinds of translation equivalence in the translations.Keywords: translation, translation method, translation equivalence, short story